2007
DOI: 10.1016/j.cardiores.2006.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Pro- and antiarrhythmic properties of a diet rich in fish oil

Abstract: Increased consumption of fish rich in omega-3 polyunsaturated fatty acids (omega3-PUFAs) is associated with decreased incidence of sudden cardiac death in post-myocardial infarction patients, but is also related to increased incidence of sudden death and arrhythmias in patients with acute myocardial ischemia. This review discusses the possible pro- and antiarrhythmic mechanisms of omega3-PUFAs in relation to various cardiac pathologies. Differences between circulating and incorporated omega3-PUFAs with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
102
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 67 publications
1
102
0
Order By: Relevance
“…However, contrary to reports of the beneficial effects of 3FA consumption or supplements on cardiac deaths in some populations (14), other trials have suggested a neutral effect in patients with implanted cardioverter defibrillators (7,35) and even a deleterious effect in men with angina (8). It is unclear whether these contradictory observations on the effects of 3FA supplementation can be accounted for by different population characteristics (e.g., angina vs. post-myocardial infarction or heart failure), possible toxic effects of mercury exposure associated with fish intake, background fish consumption in the control population, or the type of arrhythmogenic mechanism (e.g., triggered activity vs. reentry arrhythmias) (12).…”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to reports of the beneficial effects of 3FA consumption or supplements on cardiac deaths in some populations (14), other trials have suggested a neutral effect in patients with implanted cardioverter defibrillators (7,35) and even a deleterious effect in men with angina (8). It is unclear whether these contradictory observations on the effects of 3FA supplementation can be accounted for by different population characteristics (e.g., angina vs. post-myocardial infarction or heart failure), possible toxic effects of mercury exposure associated with fish intake, background fish consumption in the control population, or the type of arrhythmogenic mechanism (e.g., triggered activity vs. reentry arrhythmias) (12).…”
Section: Discussionmentioning
confidence: 99%
“…Acutely administered PUFAs have a number of effects on cardiac ion channels and transporters, which may differ in important ways from chronically administered PUFAs that are gradually incorporated into the cell membrane. 11 PUFAs may have complex effects that are proarrhythmic, antiarrhythmic, or neutral, depending on the mode of administration and arrhythmia mechanism. 11,12 Acutely administered PUFAs have been reported to reduce stretch-induced susceptibility to AF in isolated rabbit hearts 13 and to suppress short-term (several-hour) atrial tachycardia remodeling in dogs.…”
Section: Clinical Perspective P 2109mentioning
confidence: 99%
“…11 PUFAs may have complex effects that are proarrhythmic, antiarrhythmic, or neutral, depending on the mode of administration and arrhythmia mechanism. 11,12 Acutely administered PUFAs have been reported to reduce stretch-induced susceptibility to AF in isolated rabbit hearts 13 and to suppress short-term (several-hour) atrial tachycardia remodeling in dogs. 14 However, no published information is available on sustained oral PUFA administration, as occurs with dietary fish oil, on animal models of clinically relevant AF substrates like those induced by longer-term atrial tachypacing (ATP) and ventricular tachypacing (VTP)-induced congestive heart failure (CHF).…”
Section: Clinical Perspective P 2109mentioning
confidence: 99%
“…2 We cannot exclude I Na,P in human myocytes, although similarity of the response to 3-polyunsaturated fatty acids makes species differences less probable. In addition, reductions in [Ca 2ϩ ] i levels after application of 3-polyunsaturated fatty acids have been observed in isolated myocytes from both healthy and diseased hearts 1,3,4 and are therefore likely independent of I Na,P .…”
mentioning
confidence: 99%
“…[3][4][5] Therefore, we excluded the possibility that the antiarrhythmic mechanism of 3-polyunsaturated fatty acids is related to inhibition of I Na,P , at least in the rabbit model of heart failure.…”
mentioning
confidence: 99%